Pengaruh Kualitas Produk dan Citra Merek terhadap Niat Beli Smartphone Xiaomi - Mahshun, Ahmad; Indarwati, Tias Andarini (Jurnal Ilmu Manajemen, 2022)
The development of increasingly sophisticated smartphone communication technology impacts increased smartphone users in Indonesia. One of the smartphones in great demand is Xiaomi the Xiaomi smartphone is one of the brands with good product quality and is widely known in Indonesia. The type of research used is quantitative. The number of respondents used was 100 respondents who knew about Xiaomi smartphones. The sampling technique used was non-probability sampling with a purposive sampling method obtained through an online questionnaire. The analysis technique used is multiple linear regression, aiming to test the effect between variables. This study's results indicate a significant positive impact between product quality and brand image on consumer purchase intentions. The higher the product quality and brand image of Xiaomi smartphones, the higher consumers' purchase intentions for Xiaomi smartphones. This research implies that smartphone brands should pay attention to product quality and brand image, especially regarding advanced features and high specifications, but at an affordable price.